Use of probiotics as an adjuvant to sequential H. pylori eradication therapy: impact on eradication rates, treatment resistance, treatment-related side effects, and patient compliance - Ayhan Hilmi Çekin; Yasin Şahintürk; Ferda Akbay Harmandar; Seyit Uyar; Başak Oğuz Yolcular; Yeşim Çekin (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To evaluate the effect of probiotics administered as an adjuvant to sequential Helicobacter pylori (H. pylori) eradication therapy on treatment outcome and patient compliance. Materials and Methods: In total, 159 patients with H. pylori infection receiving sequential H. pylori eradication therapy were included in this randomized placebo-controlled study. Starting from day 0 of sequential eradication therapy (ERA), patients in the ERA+probiotic group [n=53, mean (SD) age: 47.7 (14.0) years, 54.7% were females] also received a probiotic supplement with Bifidobacterium animalis subsp. lactis B94 (1 capsule/day), patients in the ERA+placebo group [n=52, mean (SD) age: 46.4 (13.4) years, 51.9% were males] received placebo treatment (1 capsule/day), and patients in the ERA-only group [n=54, mean (SD) age: 46.3 (11.9) years, 55.6% were females] received no additional treatments. Eradication rates, patient compliance, and side effects of eradication therapy were recorded in each treatment group. Results: Significantly higher eradication rates were noted in the ERA+probiotic group (86.8% vs. 70.8%, p=0.025) than in the combined ERA (ERA-only and ERA-placebo) group. Non-compliance with anti-H. pylori treatment was noted in 24 (15.1%) of 159 patients. Lower rates of first week treatment non-compliance due to diarrhea (1.88% vs. 12.26%, p=0.036) were noted in the ERA+probiotic group than in the combined ERA (ERA-only and ERA-placebo) group. Treatment resistance (p: 0.389) was similar between the groups, indicating pure antibiotic resistance without any compliance problems. The number needed to treat for an additional beneficial outcome (NNTB) was 6.2 (CI 95%, 3.5 to 28.9) for probiotic use. Conclusion: In conclusion, adjuvant administration of probiotic (B. animalis subsp. lactis) in 2-week sequential H. pylori eradication therapy is associated with a higher H. pylori eradication rate, lower first week diarrhea-related treatment discontinuation rates, less common self-reported side effects, and higher treatment compliance.